(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Driving all the way up is a hassle for drivers because it will consume their time going all the way up just to go to the parking destination; that’s why the researchers conducted this title, Car elevator parking, to lessen the time drivers drive all the way on a spiral highway. A car elevator is a platform that carries a car up and down; if a human has an elevator, a car has it too. After running some tests and using the right methods, the project works well, and the elevator works up and down. The elevator is a platform that carries a car up or down to move it up and down. First, the researcher’s car needed an Arduino; an Arduino will be the motherboard to make all components in the prototype work their specific task to make all the components work. The components will need a jumper wire that is used to connect every component to the Arduino to make their specific task work.